Roads Leading to Self-Employment: Comparing Transgenerational Entrepreneurs and Self-Made Start-Ups - Boris F. Blumberg; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2015)
This paper studies the event history of business foundation. Three theoretical concepts of human, financial and social capital are linked to investigate variations over time of people's decision processes to become self-employed. Data from a cohort of Dutch inhabitants born in 1939/1940 who have been interviewed three times during their lives in 1952, 1983, and 1993 allows for testing theoretical hypotheses that state clear differences between two different roads towards business ownership. Empirical results show that the baseline hazard decreases with time for transgenerational entrepreneurs with self-employed parents, but increases for self-made startups. Social capital in the form of strong ties is a better predictor of enterprise than human capital.
Keywords: D92; M14; M21; 330; entrepreneurship; family business; new venture creation